Assessing community relocation and resettlement programs for managing conflicts in the prestea mining community - Adonteng-Kissi, O.; Ohene-Konadu, K. (International Journal of Sustainability Policy and Practice, 2015)
The application of community relocation and resettlement programs as conflict management frameworks has done little to mitigate land use conflicts in the catchment areas of Ghana’s Prestea mining community. This assertion is made in light of persisting occasional clashes between Prestea’s large-scale mines and local community members. Community relocation and resettlement programs have been put together by the Government of Ghana and large-scale mining firms as tools for managing land use conflicts. However, there is uncertainty surrounding the effectiveness of the community relocation and resettlement programs in the face of the continuing conflicts. Conducting a thorough assessment of the impacts of the community relocation and resettlement programs is critical. This study questions the potency of these programs by assessing their effectiveness. This study shows that the programs are ineffective in managing conflicts because the government and large-scale mining companies often cause severe community disruption and hinder the development of other potentially profitable industries of the Prestea Community such as farming, smallscale indigenous mining, and small-scale fishing. © Common Ground, Obed Adonteng-Kissi, Kofi Ohene-Konadu, All Rights Reserved.
Keywords: Conflict Management; Framework; Galamsey; Mining Communities; Small-Scale Mining